The effectiveness of digital multimedia presentation of trial information on recruitment and retention of patients: Protocol for a study within a trial (SWAT). - Duane, Sinead (HRB Open Res, 2020)
Background: Studies within trials (SWATs) present an opportunity to examine design factors that may impact on the successful delivery of trials. One area in need of research is trial recruitment. Recruiting patients to trials is a major challenge facing trialists. Failure to meet recruitment targets can result in delays and underpowered studies. This SWAT evaluates the effectiveness of hand-held digital multimedia presentation of trial information and standard written patient information to potential participants on recruitment and retention to a host trial. Methods: This is the protocol for SWAT 15, a two-group, embedded parallel randomised controlled trial (RCT) (ISRCTN12838042) designed within a host trial - the SATIN trial (ISRCTN88111427), a RCT designed for implementation in the Irish primary care setting. The SWAT eligibility criteria was determined by the host trial. General practices who agree to participate in the host trial will provide women (participants) who are willing to consider participating in the host trial with either a multimedia digital information resource facilitated through a handheld tablet device, plus a written participant information leaflet (Intervention) or a written participant information leaflet (comparator). Outcomes are recruitment and retention to the host SATIN trial and participant’s quality of decision-making. Discussion: Although designed to be implemented in a host trial, the host trial, was suspended and therefore this SWAT was not implemented. The protocol and the lessons learnt whilst developing it offer guidance to researchers who wish to answer similar research questions in the future in a similar context or setting.   Trial registration: ISRCTN Registry ISRCTN12838042 (11/10/2017)